Benefits of Good Quality Service in Customer Engagement in Selected Fast Food Chain in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In this study, the researchers are trying to investigate the benefits of good quality service incustomer engagement in selected fast food chains in Quezon City. This is how the companycreates a relationship with its customers. This study was conducted in order to investigate thedegree of satisfaction level of customers after experiencing fast food service located inQuezon City. Fast food Chain is one of the most successful businesses in the Industry. A fast-food restaurant, also known as a quick-service restaurant (QSR) in the industry, is a specifictype of restaurant that serves fast-food meals. It operates and provides standardizedingredients and/or partially prepared foods. Fast food is one of the fastest growing industriesin the world, so today’s generation of people is aiming to have a food business with a new andunique taste to the people; people are likely fans of eating foods that are new to them. But onbehalf of that there are some issues spreading about services and safety of food some fastfood is dealing many complaints from their customers because of bad service, notapproachable, the way the employee talk to their customers, and not granting the request ofthe guest. This kind of service will affect the company. On the other hand, some fast foodcompanies provide good quality service to their customers because they know that it willbenefit them. They provide the best service they can. In order to provide good quality service,the industry should make efforts to make service quality a benchmark for every customer togain a competitive advantage in the restaurant market.Some of the customers encountered good service, and some of them didn’t. Based on theanalysis, it was discovered that most of the respondents said that the fast food chain lacksquality service when it comes to providing standard products to the customers. They mustchange and improve their service for the satisfaction of the customers who eat in their store.Therefore, the overall results of the survey, the store should focus on providing qualityproducts and prioritize the needs of the customers. Accuracy and consistency of theemployees towards their customers are the best practices to have successful quality service.Based on the conclusions presented, this study came up with the discussion to recommendthe best way to improve the negative feedback of the customers; this fast food lacks providinggood quality products on time; therefore, the customers didn’t reach the satisfaction that theyexpect to happen. Especially based on the findings of the analysis, the store is more focusedon having Gen Z and Millennial customers. Nowadays, this generation is eager to get whatthey deserve when money and food are involved. Also, the store should put more effort intoapproaching the customers so they feel they are valued. Feedback is helpful. It is the best wayto know the wants and dislikes of the customers to avoid complaints.
Keywords: Hospitality Management